Indigenous thinking and historical knowledge: reflections on the functions of history teaching (PerCursos, 2021)
This paper’s objective is thinking about the possible dialogues between theoretical production of indigenous authors and History’s teaching, an intention that is based on the demands driven by the 11.645/2008 law. This legal measure has made the study of indigenous peoples in Brazilian educational institutions mandatory in 2008. The text structure is divided between two parts: the first one contextualizes and analyzes some aspects related to the law and also to its Operational Guidelines, published in 2016. The second part is dedicated to deepen the theoretical features of teaching indigenous History based on the discussions presented for historical education, focusing on the perspective of indigenous narratives and their contributions to historiography and teaching. Thus, the present text focuses on the two dimensions of teaching indigenous history, which are both its social and cognitive function, and to achieve this aim, it based on indigenous authors as Ailton Krenak, Gersem Baniwa and Peter Lee.
Keywords: Law 11.645/ 2008; Indigenous authors; History teaching